2015
DOI: 10.1111/infa.12126
|View full text |Cite
|
Sign up to set email alerts
|

Vois‐Tu Le Kem? Do You See the Bos? Foreign Word Learning at 14 Months

Abstract: How easily can infants regularly exposed to only one language begin to acquire a second one?In three experiments, we tested 14-month-old English and French monolingual infants' ability to learn words presented in foreign language sentence frames. Infants were trained on two novel word-object pairings and then tested using a preferential looking task. Word forms were phonetically and phonotactically legal in both languages, and cross-spliced across conditions, so only the sentence frames established the word as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
2
1
Order By: Relevance
“…These findings are unexpected and contrast with previous studies that have reported successful word learning for monolingual 14-month-olds using isolated words (Werker et al, 1998) and sentence frames (da Estrela & Byers-Heinlein, 2016;Fennell & Waxman, 2010). Importantly, our task was designed to be easy and conducive to word learning.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are unexpected and contrast with previous studies that have reported successful word learning for monolingual 14-month-olds using isolated words (Werker et al, 1998) and sentence frames (da Estrela & Byers-Heinlein, 2016;Fennell & Waxman, 2010). Importantly, our task was designed to be easy and conducive to word learning.…”
Section: Discussioncontrasting
confidence: 99%
“…The visual stimuli had been used in prior research examining word learning in monolingual and bilingual infants (Byers-Heinlein et al, 2013;Curtin et al, 2009;Fennell & Waxman, 2010). The auditory stimuli were recorded in our lab and were previously used in an experiment on word learning with monolingual infants (da Estrela & Byers-Heinlein, 2016).…”
Section: Stimulimentioning
confidence: 99%
“…A similar effect was found earlier in development, in French- and English-learning infants aged 1;2 tested on their ability to learn words presented in either French or English sentences (da Estrela & Byers-Heinlein, 2016). When taught one native and one nonnative word, infants could learn both of them equally well, extending infants’ ability to learn words in a nonnative language at a younger age.…”
Section: Introductionsupporting
confidence: 74%
“…In both Bijeljac-Babic et al . (2009) and da Estrela and Byers-Heinlein (2016), the two languages contrasted (French and English) were typologically relatively similar (both being Indo-European languages), though infants should distinguish them based at least on rhythmic properties (e.g., Mehler, Jusczyk, Lambertz, Halsted, Bertoncini & Amiel-Tison, 1988; Nazzi, Bertoncini & Mehler, 1998). Would the ability to learn new words extend to more typologically distant nonnative languages?…”
Section: Introductionmentioning
confidence: 99%